Review of O. Varon-Vassard's Η ανάδυση μιας δύσκολης μνήμης. Κείμενα για τη γενοκτονία των Εβραίων [The emergence of a difficult memory: Texts on the genocide of the Jews] - Gazi, Effi (Historein, 2013)
Odette Varon-Vassard, Η ανάδυση μιας δύσκολης μνήμης. Κείμενα για τη γενοκτονία των Εβραίων [The emergence of a difficult memory: Texts on the genocide of the Jews], Athens: Estia, 2013 (2nd exp. ed.), 230 pp